Recurrent Cholangitis From Common Bile Duct Stones After Cholecystectomy in A Patient With Duodenal Periampullary Diverticula (Bangladesh Journal of Medicine, 2025)
Choledocholithiasis is a commonly encountered hepatobiliary disease. The gallstones may migrate into the common bile duct (CBD) or develop de novo in the CBD. Endoscopic Retrograde Cholangiopancreatography (ERCP) is the primary treatment for choledocholithiasis with reduced morbidity and similar efficacy compared to surgical exploration of the common bile duct. Some anatomic factors that promote biliary stasis include CBD dilation, periampullary diverticulum, and CBD stricture. We reported on a 61-year-old patient who underwent multiple ERCPs for recurrent cholangitis due to CBD stones. Each time she had fever, abdominal pain and jaundice. Periampullary duodenal diverticula were a risk factor for recurrent stone formation. Choledochoduodenostomy was performed to prevent recurrent CBD stone formation. At endoscopic follow-up, healed diverticula were noted.Bangladesh J Medicine 2025; 36(3): 155-159